The impact of Basel III implementation on the financial performance of the banking industry in Bangladesh - Nafis Yamin; Mostafa Asif; Md. Abu Hasnat; Mohammed Monzurul Islam; Muhammad Nasiruddin; Hissan Khandakar; Md. Azizur Rahman (Banks and Bank Systems, 2025)
The implementation of Basel III regulations has become a crucial factor influencing the financial performance of the banking sector in Bangladesh. The primary objective of this study is to examine the impact of Basel III implementation on the financial performance of the banking industry in Bangladesh. The research utilizes secondary data from 20 commercial banks in Bangladesh, including state-owned, private, and Islamic banks. It offers a diverse and representative sample of Bangladesh’s banking sector, covering the period from 2014 to 2023. This variety ensures a comprehensive understanding of different banking models and their challenges, representing the scenario of the whole industry. A multivariate regression model with fixed effects, determined by the Hausman test, was employed to analyze the relationship between capital adequacy (CRAR, Core Capital Tier-1, Tier-1, and Tier-2 Capital Ratios) and bank-specific factors (size, provisions) on performance indicators (ROA and NPL). The findings reveal that higher capital adequacy, particularly the Tier-1 Capital Ratio, and CRAR, positively influences bank profitability (measured by ROA) and reduces NPLs. Conversely, larger bank size correlates with lower ROA and higher NPLs, and increased provisions also lead to higher NPLs. These results underscore the significance of Basel III in enhancing the financial performance and stability of the banking sector in Bangladesh, suggesting that more substantial capital buffers can improve profitability and reduce risks associated with non-performing loans.